Sistem Outsourcing Dalam Hubungan Industrial Di Indonesia (Outsourcing System In Industrial Relation In Indonesia) - Anak Agung Prabhaputra; I Nyoman Putu Budiartha (Scopus ID: 57202765630); I Putu Gde Seputra (Jurnal Analogi Hukum, 2019)
Abstract In the world of intense business competition, companies are increasingly required to be more flexible in responding to market demand and maintaining competitiveness which is a competitive focus. The outsourcing strategy is the answer to that, but in Indonesian Law (Undang-Undang) Number 13 of 2003 concerning Manpower which regulates this outsourcing system, factually it does not guarantee legal certainty related to type of work and employment relations carried out by outsourced workers, where this of course will have an effect on harmonious industrial relations by business people (outsourcing companies atau job recipients, outsourcing companies atau employers and laborers atau outsourced workers) as well as legal certainty for the protection of outsourced workers atau laborers itself. The problem in this essay is 1. What is the arrangement of the outsourcing system according to Indonesian laws and regulations? 2. What is the industrial relation to workers in the outsourcing system? By using normative research methods that refer to legislation and conceptual approaches, this research is expected to provide solutions to problems in employment and as a reference in finding a system of good industrial relations cooperation that is also mutually beneficial, as well as a foundation in improving or constructing the Law. Labor Law in Indonesia. Keywords: Industrial Relations; Legal Certainty; Outsourcing Abstrak Dalam dunia persaingan usaha yang ketat, perusahaan semakin dituntut untuk lebih fleksibel dalam merespon permintaan pasar dan mempertahankan daya saingnya yang menjadi fokus utama kompetitif. Strategi outsourcing (alih daya) merupakan jawaban akan hal itu, namun dalam Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan yang mengatur tentang sistem outsourcing ini, secara faktual tidaklah menjamin kepastian hukum terkait dengan jenis pekerjaan dan hubungan kerja yang dilakukan oleh pekerja atau buruh outsourcing, dimana hal ini tentunya akan berpengaruh terhadap hubungan industrial yang harmonis oleh para pelaku usaha (perusahaan penyedia outsourcing atau penerima pekerjaan, perusahaan pengguna outsourcing atau pemberi pekerjaan dan buruh atau pekerja outsourcing) serta kepastian hukum terhadap perlindungan bagi pekerja atau buruh outsourcing itu sendiri. Permasalahan dalam skripsi ini adalah 1. Bagaimanakah pengaturan sistem outsourcing (alih daya) menurut peraturan perundang-undangan di Indonesia? 2. Bagaimanakah hubungan industrial terhadap pekerja dalam sistem outsourcing (alih daya)? Dengan menggunakan metode penelitian normatif yang mengacu pada peraturan perundang-undangan dan pendekatan konseptual, skripsi ini diharapkan bisa memberikan solusi atas permasalahan dalam ketenagakerjaan dan sebagai acuan dalam mencari sistem kerjasama hubungan industrial yang baik juga saling menguntungkan, serta sebagai pondasi dalam memperbaiki atau mengkonstruksi Undang-Undang Ketenagakerjaan di Indonesia. Kata kunci: Hubungan Industrial; Kepastian Hukum; Outsourcing